Antioxidant activities and contents of free, esterified and insoluble-bound phenolics in 14 subtropical fruit leaves collected from the south of China. (March 2017) - Chen, Guan-Lin; Zhang, Xin; Chen, Song-Gen; Han, Men-Di; Gao, Yong-Qing
Highlights: Antioxidant capacities and free, esterified and insoluble-bound polyphenols were determined. Rutin, isoquercitrin, quercitrin and quercetin were widely found in these fruit leaves. Fruit leaves were source of polyphenols and antioxidants. Abstract: In order to explore the potential of different subtropical fruit leaves as natural sources of bioactive compounds, free, esterified and insoluble-bound forms of total phenolic contents (TPC) and total flavonoid contents (TFC) were determined. The antioxidant activities of fruit leaves was determined by 2, 2-diphenyl-1-picrylhydrazyl radical scavenging activity (DPPH), ferric reducing antioxidant power (FRAP), and trolox equivalent antioxidant capacity (TEAC) assays. Furthermore, several phenolic compounds were detected using ultra performance liquid chromatography (UPLC) technique. Rutin, (+)-catechin, isoquercitrin, quercitrin and quercetin were widely found in these fruit leaves. The highest TPC, TFC and antioxidant capacities were found in Averrhoa carambola, Dimocarpus longgana Lour, Litchi chinensis Sonn, Mangifera indica and Psidium guajava Linn . The results implied that these leaves are important natural sources of antioxidants for preparing functional food ingredients and preventing oxidative stress diseases.